Consensus validation of the POSAMINO (POtentially Serious Alcohol–Medication INteractions in Older adults) criteria. Issue 11 (8th November 2017) - Holton, Alice E; Gallagher, Paul J; Ryan, Cristín; Fahey, Tom; Cousins, Gráinne
Abstract : Objectives: Older adults are particularly vulnerable to adverse effects from concurrent alcohol and medication use. However, there is limited evidence regarding the prevalence of these adverse outcomes among older adults, and there is a lack of consensus regarding what constitutes an alcohol-interactive medicine. The objective of this study was to develop an explicit list of potentially serious alcohol–medication interactions for use in older adults. Design: Following a systematic review, review of drug compendia and clinical guidance documents, a two-round Delphi consensus method was conducted. Setting: Ireland and the United Kingdom (UK), primary care and hospital setting. Participants: The Project Steering Group developed a list of potentially serious alcohol–medication interactions. The Delphi panel consisted of 19 healthcare professionals (general practitioners, geriatricians, hospital and community pharmacists, clinical pharmacologists and pharmacists, and physicians specialising in substance misuse). Results: An inventory of 52 potentially serious alcohol–medication interactions was developed by the Project Steering Group. British National Formulary black dot warnings (n=8) were included in the final criteria as they represent 'potentially serious' interactions. The remaining 44 criteria underwent a two-round Delphi process. In the first round, 13 criteria were accepted into the POtentially Serious Alcohol–Medication INteractions in Older adults (POSAMINO) criteria. Consensus was not reached on the remaining 31 criteria; 9 were removed and 8 additional criteria were included following a review of panellist comments. The remaining 30 criteria went to round 2, with 17 criteria reaching consensus, providing a final list of 38 potentially serious alcohol–medication interactions: central nervous system (n=15), cardiovascular system (n=9), endocrine system (n=5), musculoskeletal system (n=3), infections (n=3), malignant disease and immunosuppression (n=2), and respiratory system (n=1). Conclusions: POSAMINO is the first set of explicit potentially serious alcohol–medication interactions for use in older adults. Following future validation studies, these criteria may allow for the risk stratification of older adults at the point of prescribing.